Novel Nanomaterials Synthesis and Applications - Kyzas, George Z.; Mitropoulos, Athanasios C. (IntechOpen, 2018)
"Nanomaterials" is a special topic of recent research and is a milestone of nanoscience and nanotechnology. Nanoscale materials are a series of substances/compounds, in which at least one dimension has smaller size than 100 nm. Nanomaterials have a broad area of development, which is growing rapidly day by day. Their impact on commercial applications as well as on the respective academia and education is huge. The basic points of this book can be divided into synthesis of nanomaterials and their applications. For example, special mention is about metal-oxide nanostructures, nanocomposites, and polymeric nanomaterials. Also, synthesis, characterizations, various processes, fabrications and some promising applications are also developed and analyzed.